2018
DOI: 10.1515/ijamh-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of concussion, but low knowledge levels among young adults

Abstract: Cerebral concussion is a brain injury, that involves a complex pathophysiological process that affects the brain as a result of biomechanical forces. With the increasing prevalence, it is important that the public is knowledgeable about concussion and its symptoms, so that they can bring attention to individuals with concussion symptoms soon after onset, for appropriate care. The aim of this study was to determine the knowledgeability of young adults. Secondary aims were to compare the knowledgeability of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Overall, previous studies identified poor levels of BC knowledge in various aspects such as post-concussive symptoms, identification, recovery and management after the BC 3,17,19,20,34,35 . For example, McKinlay et al 21 reported that there was significant uncertainty in the general population about what a BC is and how it should be managed.…”
Section: Brain Concussion Knowledgementioning
confidence: 90%
“…Overall, previous studies identified poor levels of BC knowledge in various aspects such as post-concussive symptoms, identification, recovery and management after the BC 3,17,19,20,34,35 . For example, McKinlay et al 21 reported that there was significant uncertainty in the general population about what a BC is and how it should be managed.…”
Section: Brain Concussion Knowledgementioning
confidence: 90%